Insights Into Platelet-Derived MicroRNAs in Cardiovascular and Oncologic Diseases: Potential Predictor and Therapeutic Target - Leng, Qianru; Ding, Jie; Dai, Meiyan; Liu, Lei; Fang, Qing; Wang, Dao Wen; Wu, Lujin; Wang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Non-communicable diseases (NCDs), represented by cardiovascular diseases and cancer, have been the leading cause of death globally. Improvements in mortality from cardiovascular (CV) diseases (decrease of 14%/100 000, USA) or cancers (increase 7.5%/100 000, USA) seem unsatisfactory during the past two decades, and so the search for innovative and accurate biomarkers of early diagnosis and prevention, and novel treatment strategies is a valuable clinical and economic endeavor. Both tumors and cardiovascular system are rich in angiological systems that maintain material exchange, signal transduction and distant regulation. This pattern determines that they are strongly influenced by circulating substances, such as glycolipid metabolism, inflammatory homeostasis and cyclic non-coding RNA and so forth. Platelets, a group of small anucleated cells, inherit many mature proteins, mRNAs, and non-coding RNAs from their parent megakaryocytes during gradual formation and manifest important roles in inflammation, angiogenesis, atherosclerosis, stroke, myocardial infarction, diabetes, cancer and many other diseases apart from its classical function in hemostasis. MicroRNAs (miRNAs) are a class of non-coding RNAs containing 22 nucleotides that participate in many key cellular processes by pairing with mRNAs at partially complementary binding sites for post-transcriptional regulation of gene expression. Platelets contain fully functional miRNA processors in their microvesicles and are able to transport their miRNAs to neighboring cells and regulate their gene expression. Therefore, the importance of platelet-derived miRNAs for the human health is of increasing interest. Here, we will elaborate systematically the roles of platelet-derived miRNAs in cardiovascular disease and cancer in the hope of providing clinicians with new ideas for early diagnosis and therapeutic strategies.